Resistance of Geographical Strains of German Cockroach Blattella germanica (L.) (Dictyoptera: Blattellidae) to some insecticides that using in northeast Libya. - Amer , A. M.; EL-Awami, F. o. (Al-Mukhtar Journal of Sciences, 2000)
This study performance for purpose to give enough knowledge about situation of Diazinon, Chlorpyrifos and Cyprmethrin resistance in five geographical strains from German cockroach Blattella gernianica (Linnaeus) were collected from five cities belong northeast Libya, they are Benghazi EL-Maij EL-Bieda Durna and Tobruk, compared with laboratory susceptible strain. The insects treated by use method of (W.H.O.) to resistance measurement. The results indicate that, the Tobruk strain (number 5) was more resistance to organic phosphors insecticides Diazinon and Chlorpyrifos than other strains, While the two strains EL-Bieda strain (number 3) and Durna strain (number 4) ware show high resistance against Pyrethroid insecticide Cypermethrin than remainder strains.